Critical Linguistics Principles in the Writings of Bishr Ibn Mutamar: معايير لسانية نقدية في صحيفة بشر بن المعتمر - Abbas, Dr. Muhammad Zubair; Nawaz, Dr. Habib; Al-Rasheedi, Dr. Muhammad Ayub (Al Khadim Research Journal of Islamic Culture and Civilization, 2021)
Jāḥiẓ is the major source who had discovered the knowledgeable personality, well experienced critic and rhetorical Bishr in his two first-hand books: al-Bayan and al-Hayawan. He took quotes of Bishr in a few pages which were full of Bishr’s concepts and ideas. These few pages became more ideological referring to all the rest of critical world after his death. Scholarly Bishr is considered the first ever ideological teacher of al-Jāḥiẓ. And he is well known figure in the stylistics or rhetorics. Bishr in these few pages disclosed many textual, linguistic and other multi-phenomenal linguistics and literature based ideas and concepts that later had been the keys to all the rest of world of Arabic literature, particularly, Arabic rhetoric. These key ideas become more fundamental when they are compared with today’s advancement of westernized linguistics because there are so and so matching keywords proving at all that all these things are not new but they actually represent shades of those concepts that were introduced in the earlier time. In this paper these ideas that are more popular in rhetoric and critic fields will be discussed in details.